2018
DOI: 10.1093/annweh/wxx099
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Thai Agricultural Workers’ Health, Working Conditions, and Pesticide Use by Farm Type

Abstract: More than 11 million Thai people (38%) work in agriculture, but since most are in the informal sector, government enforcement and support are very limited. As a result, working conditions on Thai farms vary greatly, putting the health of many agricultural workers at risk. A cross-sectional study in three Thai provinces collected information on the work activities and conditions of 424 farmers representing five farm types: rice, vegetable, flower, rice/vegetable, and flower/vegetable. The agricultural workers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 21 publications
7
27
2
4
Order By: Relevance
“…Thereby may be more vulnerable to adverse effects, especially pesticide poisoning ( Ward et al, 2006 ; Shirangi et al, 2011 ; Parks et al, 2016 ). The chronic diseases reported by pesticide-exposed participants in our study is in agreement with studies performed in similar conditions (directly and indirectly exposition) ( Mrema et al, 2017 ; Kongtip et al, 2018 ; Barrón-Cuenca et al, 2019 ). Moreover, other epidemiological studies have shown a higher risk of psychiatric problems, in people exposed to pesticides – especially those who have suffered from pesticide poisoning – in different countries such as Chile ( Corral et al, 2017 ), Egypt ( Rohlman et al, 2019 ), Korea ( Koh et al, 2017 ), Mexico ( Serrano-Medina et al, 2019 ), and Brazil ( Meyer et al, 2010 ; Farias et al, 2014 ; Campos et al, 2016 ; Nascimento et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thereby may be more vulnerable to adverse effects, especially pesticide poisoning ( Ward et al, 2006 ; Shirangi et al, 2011 ; Parks et al, 2016 ). The chronic diseases reported by pesticide-exposed participants in our study is in agreement with studies performed in similar conditions (directly and indirectly exposition) ( Mrema et al, 2017 ; Kongtip et al, 2018 ; Barrón-Cuenca et al, 2019 ). Moreover, other epidemiological studies have shown a higher risk of psychiatric problems, in people exposed to pesticides – especially those who have suffered from pesticide poisoning – in different countries such as Chile ( Corral et al, 2017 ), Egypt ( Rohlman et al, 2019 ), Korea ( Koh et al, 2017 ), Mexico ( Serrano-Medina et al, 2019 ), and Brazil ( Meyer et al, 2010 ; Farias et al, 2014 ; Campos et al, 2016 ; Nascimento et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although sugarcane cutting is physically demanding work [ 25 , 26 , 27 ], we found the proportion of women working in this occupation was about 40%, which is consistent with a study of sugarcane cutters in Cambodia [ 28 ]. This situation may be caused by more recent economic factors that drive rural men to move to urban areas to work in the industrial sector or in other higher paying jobs [ 22 ]. The wages of sugarcane cutters depend on how much they cut, mostly 0.5–0.7 Baht (~US Cent 1.7–2.3)/binder for burnt cane (10–16 stalks) and 1.5–2 baht (~US Cent 5.0–6.7)/binder for green cane [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For data analysis, we grouped sometimes + regularly into an “ever” variable. This questionnaire has been previously used in other studies in Thailand [ 22 , 23 , 24 ], and it is available in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…In the study on Kansas farmers done by Rosecrance and et al, about 60% of farmers reported the MSDs in the preceding 12 months [10]. These parameters are also shown by many other studies [22]. Harvest season is the most busiest duration regarding work for farmer while remaining period are quite relaxing for farmer and they are busy in others activities.…”
Section: Resultsmentioning
confidence: 76%
“…Another background factor that causes the prevalence of MSDs in farmer is age, which is shown by the relationship of age with pain occur in low back, elbow, shoulder and knee. The Osborne study indicated that the farmer's age is not a major factor of prevalence of MSDs in Farmers [22]. In the view of REBA assessment and prioritization, all the stages and phases of farming is dangerous and have potential to lead towards the musculoskeletal disorders.…”
Section: Resultsmentioning
confidence: 99%